Design of Coal Hauling System for Optimized Detection of Coal Hauler Status Based on RFId - Yoni Widhi Prihana; Mukhlishinurrahman Mukhlishinurrahman; Rosmelia Cipta Primandani (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
PT Adaro Indonesia (PT AI) is one of the biggest coal mining companies in Indonesia located in South Kalimantan. PT AI manages 8 coal stock areas called Run of Mine (ROM). Coals from ROM are transported and blended to produce final coal products. The blending process is organized by the Dispatch Team. In carrying out its operations, the Dispatch Team is supported by The Radio Frequency Identification (RFId) system. This system utilises RFId units installed along the hauling road to generate production data. This research aims to improve RFId system so that the system is able to distinguish the status of empty and loaded coal hauler. This research succeeded in increasing the reading radius of the RFId reader from 15 meters to 35 meters and also changing the existing RFId system so that one RFId unit is able to distinguish the status of empty and loaded coal hauler units. PT Adaro Indonesia (PT AI) merupakan salah satu perusahaan tambang batubara terbesar di Indonesia yang terletak di Kalimantan Selatan. PT AI mengelola 8 area stock batubara yang disebut Run of Mine (ROM). Batubara dari ROM diangkut dan dicampur untuk menghasilkan product akhir batubara. Proses pencampuran diatur oleh Tim Dispatch. Dalam menjalankan operasionalnya, Tim Dispatch disupport menggunakan sistem Radio Frequency Identification (RFId). Sistem ini memanfaatkan unit RFId yang terpasang di sepanjang jalan hauling untuk menghasilkan data produksi. Penelitian ini bertujuan untuk memodifikasi sistem RFId sehingga satu unit RFId mampu membedakan status pengangkut batubara kosongan dan muatan. Penelitian ini berhasil menambah radius pembacaan reader RFId dari 15 meter menjadi 35 meter dan juga merubah sistem RFId yang ada sehingga satu unit RFId mampu membedakan status unit pengangkut batubara kosongan dan muatan.